Common Sense vs Ilmu: Mengapa yang Terlihat Benar Belum Tentu Ilmiah? - Azzahra Maysa Salsabila; Nina Yuliana (Jurnal Kaganga: Jurnal Ilmiah Sosial dan Humaniora, 2026)
This paper is aimed at analyzing the effect of common sense in often used as a basis for judgment in daily life because it is considered practical and aligned with direct experience. However, in many situations, what appears intuitively correct may not meet the criteria for scientific knowledge. This research employs a qualitative approach through conceptual analysis and a systematic literature review od open-access journal articles published in the last five years. The result indicate that common sense is intuitive, spontaneous, and usystematic, making it susceptible to cognitive biases and emotional influences. The findings also show that low science literacy and media literacy strengthen individuals' tendency to accept information that "feels right" without scientific verification, thereby increasing the risk of misinformation. This study emphasizes the importance of a scientific approach and critical literacy as efforts to distinguish between common sense-based beliefs and accountable scientific knowledge.